2009
DOI: 10.1677/joe-08-0495
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral administration of GH induces cell proliferation in the brain of adult hypophysectomized rats

Abstract: IGF-I treatment has been shown to enhance cell genesis in the brains of adult GH-and IGF-I-deficient rodents; however, the influence of GH therapy remains poorly understood. The present study investigated the effects of peripheral recombinant bovine GH (bGH) on cellular proliferation and survival in the neurogenic regions (subventricular zone (SVZ), and dentate gyrus of the hippocampus), as well as the corpus callosum, striatum, parietal cortex, and piriform cortex. Hypopituitarism was induced in female rats b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 49 publications
4
50
0
Order By: Relevance
“…In vitro incorporation of 3 [H]-labeled thymidine demonstrated that short-time exposure to bGH enhanced the cell proliferation in adult hippocampal progenitor cells. This observation demonstrated that peripherally administrated GH may increase the number of new cells in the brain of adult rats and that the hormone may exert a direct proliferative effect on neuronal progenitor cells (Aberg et al, 2006;Aberg et al, 2009). …”
Section: The Impact Of the Somatotrophic Axis On Neuroprotectionmentioning
confidence: 81%
See 1 more Smart Citation
“…In vitro incorporation of 3 [H]-labeled thymidine demonstrated that short-time exposure to bGH enhanced the cell proliferation in adult hippocampal progenitor cells. This observation demonstrated that peripherally administrated GH may increase the number of new cells in the brain of adult rats and that the hormone may exert a direct proliferative effect on neuronal progenitor cells (Aberg et al, 2006;Aberg et al, 2009). …”
Section: The Impact Of the Somatotrophic Axis On Neuroprotectionmentioning
confidence: 81%
“…IGF-I treatment was found to promote cell genesis in the brains of adult GH-and IGF-1-deficient rodents (Anderson et al, 2002;Aberg et al, 2009). In the hippocampus, treatment with bovine GH (bGH) induced an increase in the number of BrdU/NeuN-positive cells proportionally to the recorded increase in the number of BrdUpositive cells.…”
Section: The Impact Of the Somatotrophic Axis On Neuroprotectionmentioning
confidence: 99%
“…These findings suggest that peripherally administered ghrelin enters the hippocampus and directly stimulates hippocampal neurogenesis. However, there is also a possibility that the stimulatory effect of ghrelin on hippocampal neurogenesis could be, at least in part, due to the ability of ghrelin to stimulate the somatotropic axis [6], because both GH and IGF-1 infusions have been shown to increase hippocampal neurogenesis [13,14]. To address this possibility, we examined the effect of ghrelin in the SDRs, a dwarf strain with a mutation of the GH gene resulting in absence of circulating GH [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin potently stimulates GH secretion from the anterior pituitary gland [6] and consequently increases IGF-1 secretion from the liver. Given that both GH and IGF-1 infusions have been shown to increase hippocampal neurogenesis [13,14], there is a possibility that the action of ghrelin on hippocampal neurogenesis could be, at least in part, due to the ability of ghrelin to stimulate the GH/ IGF-1 axis.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The somatotropic axis is believed to have an important impact on neuroprotection (Nyberg 2000, Nyberg & Sharma 2002 and neurogenesis (Aberg et al 2006). GH treatment has been shown to promote neurogenesis in hippocampal areas both in intact and hypophysectomized animals (Aberg et al 2009, David Aberg et al 2010. In addition, treatment with GH may attenuate age-related alterations of hippocampal plasticity (Ramsey et al 2004).…”
Section: Discussionmentioning
confidence: 99%